Answer:
Hence, the quadratic equation is:
![f(x)=-3x^2+x=-x(3x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/opk426gfx77w1cxirjfx54p05gfcc4atoq.png)
Explanation:
Let the quadratic formula be given by:
![f(x)=ax^2+bx+c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7ocbn4l6fhq9d44wxaeha6t60ls5h9hg74.png)
Now we are given the interpolating points and there corresponding values as:
(-1,-4), (0,0) and (2,-10).
this means then x=-1 f(x)=-4
when x=0 then f(x)=0
and when x=2 then f(x)=-10
so we first put x=0
then f(x)=0=c
hence c=0.
now we are left with the function:
![f(x)=ax^2+bx------(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l9sm7ja280869tmwav2rtbueol53l5ilqe.png)
Hence now we put x=-1 in equation (1)
we get:
![f(x)=a-b=-4------(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/drodpt6768u93n65zef2g99q50oyy2syd7.png)
now we put x=2
![f(x)=4a+2b=-10------(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/io1ruppy7s0rmoaz0ysioiar94coh6ssn2.png)
On solving equation (2) and (3) by elimination we get:
Multiply equation (2) by 2 and add to equation (3) we obtain;
2a-2b= -8
4a+2b= -10
---------------------------
6a=-18
⇒ a= -3 on dividing both side by 6.
Hence on putting the value of a in equation (2) we get:
b=1
Hence, the quadratic equation is:
![f(x)=-3x^2+x=-x(3x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/opk426gfx77w1cxirjfx54p05gfcc4atoq.png)